Walls and Fences: A Journey Through History and Economics - Victoria Vernon; Klaus F. Zimmermann (Global Labor Organization (GLO), 2019)
Throughout history, border walls and fences have been built for defense, to claim land, to signal power, and to control migration. The costs of fortifications are large while the benefits are questionable. The recent trend of building walls and fences signals a paradox: In spite of the anti-immigration rhetoric of policymakers, there is little evidence that walls are effective in reducing terrorism, migration, and smuggling. Economic research suggests large benefits to open border policies in the face of increasing global migration pressures. Less restrictive migration policies should be accompanied by institutional changes aimed at increasing growth, improving security and reducing income inequality in poorer countries.
Keywords: F22; F66; H56; J61; N4; 330; Walls; fences; defense; security; international migration; mobility